A Bibliometric Analysis of Vocational School Keywords Using VOSviewer - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2023)
A vocational school is a secondary education institution that prepares students to work in their fields of study. The goal of this study was to combine mapping analysis with VOSviewer software to conduct bibliometric engineering research at a vocational school. VOSviewer and Publish or Perish were the applications used in this study.